2021
DOI: 10.1590/fst.21020
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, sensory properties and in-vitro bioaccessibility of phenolics and antioxidant capacity of traditional noodles enriched with carob (Ceratonia siliqua L.) flour

Dilek DULGER ALTINER

Abstract: In this study, the use of carob flour (CF) was investigated to improve the nutritional, antioxidative, and sensory properties of the noodles produced by the traditional method. In traditional noodle production, carob flour was used as a substitute to wheat flour at six different ratios (0%-control: Cmilk, Cwater, 10-40%, CF; w/w). In the noodle samples, L* and b* decreased whereas a* value increased as the CF substitution ratio increased. Regarding the CF substitution, which was found to be a natural antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
(74 reference statements)
0
2
0
1
Order By: Relevance
“…Another effective method to measure radical scavenging activity is the ABTS radical cation decolorization assay (Dulger Altiner, 2021). This method can be used to obtain results in a short time.…”
Section: Dpph and Abts Radical Scavenging Activitymentioning
confidence: 99%
“…Another effective method to measure radical scavenging activity is the ABTS radical cation decolorization assay (Dulger Altiner, 2021). This method can be used to obtain results in a short time.…”
Section: Dpph and Abts Radical Scavenging Activitymentioning
confidence: 99%
“…Keçiboynuzu unu içeren erişteler, kontrol numunelerine kıyasla yüksek fenolik içerik, antioksidan kapasite ve in vitro biyoerişilebilirlik göstermiş olup duyusal değerlendirme sonucunda da yüksek puanlar almıştır. Geleneksel yöntemle üretilen eriştelerin besinsel özelliklerinin iyileştirilmesi ve antioksidanlarla zenginleştirilmesi tüketiciye daha fonksiyonel ve sağlıklı erişteler sunacağından, bu çalışmanın fonksiyonel gıda pazarında ürün portföyünün geliştirilmesine katkı sağlayacağı düşünülmüştür [52].…”
Section: Makarnaunclassified
“…Synthetic antioxidants such as butylated hydroxytoluene (BHT), butylated hydroxyanisole (BHA), tert-butylhydroquinone (TBHQ) and propyl gallate (PG) have been used over the years, but these are causing the problem of toxicity (Qader et al, 2011;Altiner, 2021). It has been shown that natural products present in medicinal plants are inhibitory to the deleterious effects of oxidative stress, but their antioxidant activities of natural products are lower than those of synthetic antioxidants (Sabir & Rocha, 2008).…”
Section: Introductionmentioning
confidence: 99%